2017
DOI: 10.4103/0972-0707.212243
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of mineral trioxide aggregate and biodentine as direct pulp capping agents in carious teeth

Abstract: Background:Root canal treatment has been a routine treatment option for carious exposure of the dental pulp. In the context of minimally invasive dentistry, direct pulp capping (DPC) procedure with a reliable biomaterial may be considered as an alternative provided the pulp status is favorable. Mineral trioxide aggregate (MTA), a bioactive cement with excellent sealing ability and biocompatibility is capable of regenerating relatively damaged pulp and formation of dentin bridge when used as DPC agent. Biodenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…The sample size analysis for this study was based on the primary outcome measure, which was pulp survival (clinical and radiographic) one year after intervention. Previous prospective clinical comparative trials of greater than one-year in duration have demonstrated that caries exposure, rinsing with NaOCl, and subsequent pulp capping have reported a 90% success rate [ 18 , 20 , 21 ]. Other carious pulp capping studies using saline [ 8 ] or hydrogen peroxide [ 22 ] as a pupal rinse have reported lower success of 31% and 55%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The sample size analysis for this study was based on the primary outcome measure, which was pulp survival (clinical and radiographic) one year after intervention. Previous prospective clinical comparative trials of greater than one-year in duration have demonstrated that caries exposure, rinsing with NaOCl, and subsequent pulp capping have reported a 90% success rate [ 18 , 20 , 21 ]. Other carious pulp capping studies using saline [ 8 ] or hydrogen peroxide [ 22 ] as a pupal rinse have reported lower success of 31% and 55%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Pulp protection therapies aim to maintain the vitality of the tooth in which pulp tissue has been exposed due to trauma, carious lesions, or restorative procedures. Treatment options in this situation include direct pulp capping, pulpotomy, or pulpectomy [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The other four studies recorded the postoperative pain of patients included using visual analog scale after 7 days, 1 month, 3 months, and 6 months. In addition, postoperative radiographs were taken on 3-month and 6-month recall visits to detect any apical radiolucency,[ 19 ] assessed the pulpal health after 3 weeks, 3 months, 6 months, and 1 year using thermal and electrical pulp sensitivity testing, and in addition, 6-month follow-up radiographs were taken,[ 20 ] analyzed the clinical and radiographic recall data at intervals of 1, 3, 6, 12, and 18 months. The data were comprised pain, sensibility status of the teeth, radiographic signs of periapical pathology, and dentin bridge formation[ 21 ] and were performed clinical and radiological examination after 1-year recall.…”
Section: Resultsmentioning
confidence: 99%
“…Heterogeneity was found between the previous studies. [ 16 17 18 19 20 21 22 ] as they used different methods of evaluation (histological, clinical, and radiological), and in addition, different scores for the amount of dentin bridge formation were used in histological and radiological assessments. Pulp vitality was assessed with different parameters; moreover, dichotomous data were sometimes used, and in other instances, continuous data were the main outcome.…”
Section: Resultsmentioning
confidence: 99%